Toward Assessing and Improving Survey Questions on Religion: The ARDA's Measurement Wizard. Issue 3 (September 2014) - Bader, Christopher D.; Finke, Roger
<x xml:space="preserve">Abstract</x> Developing survey measures of religion is deceptively difficult. As religion in America becomes more diverse and research projects become more global, finding a shared vocabulary that taps into concepts of interest and selecting response categories that capture the full range of choices becomes ever more challenging. This research project introduces new tools and techniques for exploring and evaluating past survey measures of religion, including a new software tool that draws on the ARDA's massive collection of survey measures. We offer two examples to demonstrate how these resources can serve to evaluate past survey measures of religion and improve future measures.